Estudio jurídico y doctrinario de la nulidad del reconocimiento voluntario de la paternidad por existencias de vicios del consentimiento. - Guamán Contento, Jairo Raúl (2023)
The current Curricular Integration Project is titled “Legal and doctrinal study of the nullity of voluntary acknowledgment of paternity due to defects in consent” addresses the need to examine in detail the legal consequences arising from voluntary acknowledgment in cases where this act is performed under errors, deception, and bad faith by the couple (elements that constitute defects in consent). The motivation behind this research is driven by the urgent need to analyze through a doctrinal and legal study, the consequences that arise when such acknowledgment is made under error or deception (categories of defects in consent). It is crucial to understand that this legal problem has persisted for many years, as evidenced by the cases stored in the archives of different institutions throughout the country. This information can be verified on the judicial system platform. Given such circumstances, the aim is to analyze the possible consequences and infringements on rights that stem from this legal problem. To structure this research, it was established a general objective and three specific objectives. In order to validate their achievement, it was developed a conceptual framework based on extensive and selective literature and legal sources., as well as fieldwork where valuable contributions and perspectives from numerous legal professionals have been gathered. Furthermore, in this Curricular Integration Project, it was used various materials and methods to facilitate its development. Surveys and interviews were conducted with legal professionals, and the results obtained from these efforts served as the foundation for justifying the proposed reform. The primary objective is to guarantee the faithful fulfillment of rights enshrined in the Constitution and other legal frameworks.